Genetic alterations in Ki-ras and Ha-ras genes in Juvenile Nasopharyngeal Angiofibromas and head and neck cancer - Coutinho, Cláudia Malheiros; Bassini, Alessandra Simões; Gutiérrez, Leonardo Guilhermino; Butugan, Ossamu; Kowalski, Luiz Paulo; Brentani, Maria Mitzi; Nagai, Maria Aparecida (São Paulo Medical Journal, 1999)
CONETXT: Ras gene mutations have been associated to a wide range of human solid tumors. Members of the ras gene family (Ki-ras, Ha-ras and N-ras) are structurally related and code for a protein (p21) known to play an important role in the regulation of normal signal transduction and cell growth. The frequency of ras mutations is different from one type of tumor to another, suggesting that point mutations might be carcinogen-specific. OBJECTIVES: To study the occurrence of Ki-ras and Ha-ras mutations. We also studied the relative level of Ha-ras mRNA in 32 of the head and neck tumors. DESIGN: Case series. SETTING: University referral unit. PARTICIPANTS: 60 head and neck tumors and in 28 Juvenile Nasopharyngeal Angiofibromas (JNA). DIAGNOSTIC TEST: Using PCR-SSCP we examined the occurrence of Ki-ras and Ha-ras mutations. The relative level of Ha-ras mRNA was examined by Northern blot analysis. RESULTS: None of the head and neck tumors or JNA samples showed evidence of mutations within codons 12, 13, 59 and 61 of Ki-ras or Ha-ras genes. However, 17 (53%) of the tumors where gene expression could be examined exhibited increased levels of Ha-ras mRNA compared with the normal tissue derived from the same patient. CONCLUSIONS: Our results demonstrate for the first time that mutations of Ki-ras and Ha-ras genes are not associated with the development of JNA and confirm previous reports indicating that activating ras mutations are absent or rarely involved in head and neck tumors from western world patients. Furthermore, our findings suggest that overexpression of Ha-ras, rather than mutations, might be an important factor in the development and progression of head and neck tumors.